1985
DOI: 10.1002/bies.950030310
|View full text |Cite
|
Sign up to set email alerts
|

What's new: Biosensors: Current applications and future potential

Abstract: Sum ma ryBiological molecules such as enzymes and antibodies display a unique capacity to recognize and respond to other molecules in a way which can be exploited in the development of analytical devices. In a biosensor, the biological recognition system creates a physicochemical change proximal to a suitable transducer and thereby converts the concentration of the analyte into a quantifiable electrical signal. The design and construction of these devices requires an imaginative combination of biological, chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The development of analytical devices that combine the specificity and sensitivity of biological systems with appropriate electrochemical techniques is likely to have a significant impact on the health care, agricultural, environmental, security, food, pharmaceutical, and fermentation industries (1,2). Enzymatic redox reactions are particularly amenable to interfacing with electrochemical transducers since electron exchange is a key step in their natural cycle.…”
mentioning
confidence: 99%
“…The development of analytical devices that combine the specificity and sensitivity of biological systems with appropriate electrochemical techniques is likely to have a significant impact on the health care, agricultural, environmental, security, food, pharmaceutical, and fermentation industries (1,2). Enzymatic redox reactions are particularly amenable to interfacing with electrochemical transducers since electron exchange is a key step in their natural cycle.…”
mentioning
confidence: 99%
“…Phytoremediation is considered a green and sustainable method for pollutant removal. Thus, some hyperaccumulator plants were screened and had great application value in Cr phytoremediation [27][28][29][30][31][32][33][34]56]. Regretfully, the identified hyperaccumulator plants are mainly small herbs, whose average annual biomass is relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the plants applied in phytoremediation could accumulate heavy metals in organs and grow on metalliferous soils without suffering phytotoxic effects [26]. Previous reports pointed out that several species could be used for the Cr phytoremediation, such as Leersia hexandra [27], Pluchea indica, Cynodonda ctylon [28,29], Phragmites australis, Typha angustifolia [30,31], Jatropha curcas [32], Pteris vittata (Kalve et al 2011) and Spartina argentinensis [33] (Susana et al 2011). Recently, Nopalea cochenillifera was proved to be a potential Cr (VI) hyper-accumulator plant [34].…”
Section: Introductionmentioning
confidence: 99%
“…It is now eight years since the Joint Working Party of the Advisory Council for Applied Research and Development, the Advisory Board for the Research Councils and the Royal Society chaired by the late Dr Alfred Spinks reported its conclusions and recommendations on the development of biotechnology in the United Kingdom. At that time, it was hardly appreciated that a newly emerging area of pleuridisciplinary technology, biosensors, which spanned biotechnology, materials science and electronics, had the potential for making a substantial impact in a plethora of lucrative markets (Lowe 1984(Lowe , 1985Foulds & Lowe 1985). It is not, however, difficult to understand why biosensor technology has since witnessed almost exponential growth.…”
Section: T He Need For Biosensorsmentioning
confidence: 99%
“…Most successful biosensors exploit enzymes as the biological recognition/response systems, as these are known to exchange transducible components such as protons, ions, heat, light, electrons and mass as part of their catalytic mechanism (Foulds & Lowe 1985). The simplest are those whose catalysis requires or releases protons or other ions that can be coupled to an appropriate potentiometric sensor.…”
Section: Enzyme Biosensorsmentioning
confidence: 99%